FIRST RECORD OF ENDOPARASITE COLOBOMATUS ASIATICUS Hayward, 1996 (COPEPODA: POECILOSTOMATOIDA: PILICHTHYIDAE) FROM SILLAGO SIHAMA (Forsskål, 1775) FROM IRAQI MARINE WATERS - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Females of Colobomatus asiaticus Hayward, 1996 have been collected from prepercular canal of silver sillago Sillago sihama (Forsskål, 1775) from Iraqi marine waters during May 2016 and December 2017. The present work confirmed the original description of the species by possessing combination of characters: Short and rounded thoracic lobes and both third leg and genital segment with one seta. The present report Colobomatus asiaticus considered the new record from Iraq. Detail measurements of different body parts of female were given for the first time.